P44 The utility of bedside lung ultrasound in the assessment of emergency medical admissions presenting with acute dyspnoea: a prospective analysis. (15th November 2017) - Chakrabarti, B; Curtis, J; Kwok, A; Gautam, M
Abstract : Introduction: Lung Ultrasound (LUS) is emerging as a potentially useful bedside investigation to aid assessment of acute dyspnoea. However, little UK based data exists regarding the impact of LUS when performed over and above standard care in subjects presenting to hospital with acute dyspnoea. Methodology: Subjects presenting with acute dyspnoea as Emergency Admissions to 2 University Hospitals were evaluated within 24 hours of admission by a Respiratory Physician with Level 2 Ultrasound competency. A chest radiograph and appropriate blood tests had been performed beforehand. In all cases, the precise aetiology of the subject's dyspnoea remained uncertain following review of the patient/existing investigations by the Respiratory Physician but prior to bedside LUS being performed. Results: 80 subjects (Age 68 (SD 17) years; 43% Male) were included with 77 surviving to discharge. LUS findings comprised Diffuse Bilateral B lines suggestive of Acute Heart Failure (AHF)/Interstitial Syndrome in 29% (23/80), Consolidation in 23% (18/80), A lines/"normal" in 24% (19/80), unilateral focal B lines in 21% (17/80), unspecified sub-pleural focus (1/80), small pleural effusion (1/80) and loss of lung sliding/lung point indicative of pneumothorax (1/80). In the 18 cases of consolidation and the 23 cases of AHF identified on LUS, only 39% (7/18) and 30% (7/23) of the plain chest radiographs respectively were subsequently reported by a radiologist as showing any parenchymal abnormalities. In 29% (23/80) cases, the addition of LUS was felt to have given a specifically alternative diagnosis to the patient's presentation not previously considered (7/23 Pneumonia, 12/23 AHF, 2/23 Abdominal Sepsis, 1 Pneumothorax, 1 Pulmonary embolism) whilst in a further 44% (35/80) cases, LUS was felt to have strengthened the certainty of an existing differential diagnosis considered prior to LUS being performed. The diagnosis made post LUS was found to be concordant with the subject's "Discharge Diagnosis" in 83% (66/77) cases. Conclusion: Use of bedside LUS as an adjunct to standard care in the assessment of acute dyspnoea often resulted in either the consideration of an alternative diagnosis to account for a patient's symptoms or offered clinicians greater certainty on an existing differential diagnosis thus better directing management.